Pendidikan Inklusi dalam Al-Qur’an Q.S Abasa Ayat 1-11 - Ade Ifah; Ummi Nadrah Nasution; Asni Aidah Ritonga; Mohammad Al Farabi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The background is that education is a basic need for every human being, but some individuals do not receive appropriate education. Children who appear with physical differences, abilities and attitudes that are different from humans in general are often discriminated against in the education system. Building an attitude of tolerance will be effective through inclusive education in schools. The concept of inclusive education in Islamic teachings is found in the Al-Quran, which explains that humans on this earth were created with various races, ethnicities, nationalities, genders, religions and different abilities to know, appreciate and respect regardless of existing differences. In this scientific work, the researcher used the library research method by exploring various references related to the topic of discussion, namely analysis of the concept of inclusive education in the Al-Quran, Surah Abasa verses 1-11. By understanding the value of the concept of inclusive education in the Koran, you can build an attitude of social tolerance regardless of differences. Where equitable education can enable all children to have the opportunity to participate fully in regular activities regardless of any abnormalities.